A composite insulating material for high voltage cable accessories and a preparation method thereof

By using composite insulating materials of ethylene propylene rubber, reinforcement filler and quaternary ammonium salt, the problems existing in zinc oxide in the prior art are solved, and high-performance and environmentally friendly cable attachment materials are achieved.

CN116144116BActive Publication Date: 2025-02-28GLOBAL ENERGY INTERCONNECTION RES INST CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202210775244.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-01
Publication Date
2025-02-28
Estimated Expiration
2042-07-01

AI Technical Summary

Technical Problem

The existence of zinc oxide cannot be avoided in existing rubber materials, resulting in environmental pollution and degradation of performance.

Method used

Ethylene-propylene rubber, reinforcement fillers and quaternary ammonium salts are used as raw materials for composite insulating materials. The use of zinc oxide is avoided through specific ratios and preparation methods.

Benefits of technology

It realizes composite insulating materials with high electrical and mechanical properties, meets the requirements of high-voltage cable accessories, and avoids environmental pollution by zinc oxide.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116144116B_ABST
    Figure CN116144116B_ABST
Patent Text Reader

Abstract

The invention discloses a composite insulating material for high-voltage cable accessories. The raw materials include EPDM rubber, reinforcing filler and quaternary ammonium salt. The invention defines the relationship between the mass fractions of EPDM rubber, reinforcing filler and quaternary ammonium salt, and zinc oxide is not included in the raw materials of the composite insulating material. The invention also discloses a preparation method of the composite insulating material. In the invention, the quaternary ammonium salt with a specific ratio can organically modify the filler, improve the compatibility of the filler with the rubber matrix, and the quaternary ammonium salt also has the function of regulating rubber vulcanization and improving the reinforcing effect, and can replace zinc oxide in the development of rubber formulas; the EPDM rubber, reinforcing filler and quaternary ammonium salt with a specific ratio can obtain a composite insulating material with better performance, meet the use requirements of cable accessories, and avoid pollution to the environment because it does not contain zinc oxide. In the invention, the preparation method adopts a general preparation method, and the equipment will not be affected by the change of materials, which is convenient for large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of insulating rubber preparation, and in particular to a composite insulating material for high-voltage cable accessories and a preparation method thereof. Background Art

[0002] Filler-reinforced EPDM rubber has good electrical insulation properties, mainly in terms of high breakdown voltage, heat resistance and good antioxidant properties. At present, it is widely used in the insulation of high-voltage prefabricated cable accessories at home and abroad. Usually, in the process of preparing EPDM masterbatch, zinc oxide is added to the rubber as a reinforcing agent, activator, and vulcanizer for rubber vulcanization to increase the crosslinking density between rubber molecules and improve the mechanical and physical properties of the rubber. Zinc is an element close to heavy metals. When the concentration is higher than a certain value, it will pollute the environment and have adverse effects on human health, aquatic, animals and plants. Reducing the amount of zinc oxide in rubber compounds has become an important research topic. However, if the rubber compound does not contain zinc oxide, the decomposition of the vulcanization accelerator is insufficient, the vulcanization complex cannot be formed, the scorch time and vulcanization time are significantly extended, and the physical and mechanical properties are significantly reduced.

[0003] Quaternary ammonium salt is an important cationic surfactant, which is prepared by the reaction of tertiary amine and alkylating agent. There are many kinds of quaternary ammonium salt, which can be divided into single long chain quaternary ammonium salt, double long chain quaternary ammonium salt, double long chain diquaternary ammonium salt and other quaternary ammonium salts according to their different structures. Quaternary ammonium salt can carry out organic modification to filler, improve the compatibility of filler with rubber matrix. Chinese patent document CN112321952A discloses a terpolymer EPDM composite rubber material and a preparation method thereof, which adopts a modified filler obtained by alkyl quaternary ammonium salt and a coupling agent, and the base material is one or more of montmorillonite, attapulgite and vermiculite. The terpolymer EPDM composite rubber material provided by the invention can meet the requirements of high mechanical strength and low compression set at the same time, and the preparation process is simple, but the presence of zinc oxide is still unavoidable in the formula. Summary of the invention

[0004] Therefore, the technical problem to be solved by the present invention is that the defect of zinc oxide cannot be avoided in the existing rubber material raw materials, so as to provide a composite insulating material for high-voltage cable accessories and a preparation method thereof.

[0005] To this end, the present invention adopts the following technical solutions:

[0006] The present invention provides a composite insulating material for high-voltage cable accessories. The raw materials include EPDM rubber, reinforcing filler and quaternary ammonium salt. The mass fractions of the EPDM rubber, reinforcing filler and quaternary ammonium salt satisfy the following requirements:

[0007]

[0008] Wherein, a represents the mass fraction of EPDM rubber, b represents the mass fraction of reinforcing filler, and c represents the mass fraction of quaternary ammonium salt;

[0009] The composite insulating material raw material does not include zinc oxide.

[0010] Furthermore, in the raw materials,

[0011] EPDM rubber is 100 parts;

[0012] The reinforcing filler is 20-80 parts;

[0013] The quaternary ammonium salt is 0.12-3.6 parts.

[0014] The raw materials also include:

[0015] 3-5 parts of vulcanizing agent;

[0016] Additives: 5.7-46 parts.

[0017] Furthermore, the auxiliary agent includes:

[0018]

[0019] Preferably, the EPDM rubber has a Mooney viscosity of 20-55MU at ML (1+4) 100°C and an ethylene content of 45-75wt%;

[0020] The quaternary ammonium salt is at least one of cetyltrimethylammonium bromide, cetyltrimethylammonium chloride, octadecyltrimethylammonium bromide or octadecyltrimethylammonium chloride;

[0021] The reinforcing filler is at least one of white carbon black, kaolin, calcium carbonate, talcum powder or calcined clay.

[0022] The vulcanizing agent is at least one of sulfur, dicumyl peroxide or dibenzoyl peroxide;

[0023] The antioxidant is at least one of antioxidant MB and antioxidant RD;

[0024] The active agent is at least one of stearic acid, zinc stearate or calcium stearate;

[0025] The vulcanization accelerator is at least one of diphenylguanidine (vulcanization accelerator D), tetramethylthiuram disulfide (vulcanization accelerator TM), 2-mercaptobenzothiazole, triallyl isocyanurate, N-cyclohexyl-2-benzothiazole sulfenamide (vulcanization accelerator CZ), and N-tert-butyl-2-benzothiazole sulfenamide (vulcanization accelerator NS);

[0026] The plasticizer is at least one of paraffin oil, naphthenic oil or white oil;

[0027] The coupling agent is a silane coupling agent.

[0028] Further preferably, the vulcanizing agent is sulfur;

[0029] The antioxidant is antioxidant RD;

[0030] The active agent is stearic acid;

[0031] The vulcanization accelerator is at least one of diphenylguanidine (vulcanization accelerator D), tetramethylthiuram disulfide (vulcanization accelerator TT), N-cyclohexyl-2-benzothiazole sulfenamide (vulcanization accelerator CZ), and N-tert-butyl-2-benzothiazole sulfenamide (vulcanization accelerator NS);

[0032] The coupling agent is at least one of bis-(γ-triethoxysilylpropyl)tetrasulfide (Si69) and vinyl tris(β-methoxyethoxy)silane.

[0033] The present invention also provides a method for preparing the composite insulating material, comprising the following steps:

[0034] S1: Weigh the raw material components according to the ratio;

[0035] S2: adding the raw materials in sequence for mixing and kneading;

[0036] S3: performing a second-stage open refining on the first-stage mixed rubber obtained after the internal refining to obtain the composite insulating mixed rubber material;

[0037] S4: vulcanizing and drying the obtained composite insulating mixed rubber material to finally obtain the composite insulating material.

[0038] In step S2, the mixing and kneading is specifically to put the EPDM rubber into a kneading machine, knead for 2-3 minutes, the kneading speed of the kneading machine is 30-50r / min, and the kneading temperature is 80-100°C;

[0039] Add quaternary ammonium salt and active agent and continue to mix for 2-3 minutes. The speed of the mixer is 40-50r / min and the mixing temperature is 80-100℃.

[0040] Add reinforcing filler and coupling agent and mix for 3-6 minutes, the mixer speed is 40-60r / min, and the mixing temperature is 80-100℃;

[0041] Add antioxidant and plasticizer and mix for 2-6 minutes, the mixer speed is 40-60r / min, and the mixing temperature is 80-100℃;

[0042] Lower the temperature of the internal mixer, add the vulcanizing agent and vulcanization accelerator, and mix for 2-6 minutes at a speed of 30-50r / min and a mixing temperature of 50-70℃;

[0043] Debinding, debinding temperature is 50-70℃, debinding time is 1-5min;

[0044] Plasticate on the mixing mill for 2-5 minutes, with the roller distance of the mixing mill being 0.5-1.5mm, add the rubber material and pass it thinly, make triangle packages 3-5 times, slice 2-15mm, and leave it for more than 6 hours to obtain a section of mixed rubber.

[0045] In step S3, specifically, the roller spacing of the mixing mill is 0.5-1.5 mm, a thin section of mixed rubber is put into the mixing mill, and the triangular package is made 3-6 times, and the sheet is 1-10 mm, so as to obtain the composite insulating mixed rubber material;

[0046] In step S4, the vulcanization is performed by compression vulcanization at 120-180° C. and 10-20 MPa pressure for 10-20 min, and then cooled to room temperature; the drying is performed in a forced air oven at 70-90° C. for 12-18 h.

[0047] The technical solution of the present invention has the following advantages:

[0048] (1) In the present application, the quaternary ammonium salt can organically modify the filler and improve the compatibility of the filler with the rubber matrix. At the same time, the quaternary ammonium salt also has the function of regulating the vulcanization of the rubber and improving the reinforcement effect. It can replace zinc oxide in the development of rubber formula.

[0049] (2) In this application, the ratio of quaternary ammonium salt to EPDM rubber and reinforcing filler is restricted. The content of reinforcing filler has an important influence on the performance of EPDM rubber insulation material. If the content is too high, the hardness is greater than 70 shore A, and the material does not meet the installation requirements of cable accessories. If the filler content is too low, the electrical and mechanical properties of the material are low and cannot meet the application requirements of cable accessories. As an activator, quaternary ammonium salt can accelerate the vulcanization speed and improve the degree of vulcanization in this application, and can also modify and optimize the filler. Therefore, the content of quaternary ammonium salt is affected by the content of EPDM and reinforcing filler. Since quaternary ammonium salt contains quaternary ammonium groups and some double bonds, if the content of quaternary ammonium salt in the system is too high, the quaternary ammonium salt and unsaturated monomers will copolymerize, resulting in a decrease in the crosslinking density of the rubber. If the content of quaternary ammonium salt in the system is too low, the role of vulcanization activator cannot be achieved, and the effect on accelerating the vulcanization speed and improving the degree of vulcanization is small, and it cannot replace zinc oxide.

[0050] (3) The composite insulating material obtained in the present application is limited to EPDM rubber, and the final electrical performance DC breakdown strength ≥ 60kV / mm, AC breakdown strength ≥ 25kV / mm, which meets the requirements for the use of cable accessories, and because it does not contain zinc oxide, it avoids pollution to the environment.

[0051] (4) In the present application, the preparation method adopts a general preparation method, which will not affect the equipment due to changes in materials and is convenient for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0052] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0053] Figure 1 It is the vulcanization curve diagram of Example 1 and Comparative Example 1 in Test Example 2;

[0054] Figure 2 It is the vulcanization curve diagram of Example 2 and Comparative Example 2 in Test Example 2. DETAILED DESCRIPTION

[0055] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0056] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0057] Example 1

[0058] This embodiment 1 provides a composite insulating material, the chemical composition and weight fractions of which are as follows:

[0059] EPDM rubber Dow3722P: 100 parts, white carbon black: 50 parts, octadecyltrimethylammonium bromide: 1 part; stearic acid: 2 parts, antioxidant RD: 1 part, paraffin oil: 12 parts, silane coupling agent Si69: 3 parts, vulcanizing agent sulfur: 4 parts, vulcanization accelerator CZ: 1 part, vulcanization accelerator NS: 1 part.

[0060] The specific preparation method is as follows:

[0061] (1) Weigh EPDM rubber, reinforcing filler, quaternary ammonium salt, antioxidant, plasticizer, coupling agent, activator, vulcanizer and vulcanization accelerator according to the proportion.

[0062] (2) Mix white carbon black and silane coupling agent evenly.

[0063] (3) Put the EPDM rubber into an internal mixer and mix it for 2 minutes at a speed of 50 r / min and a mixing temperature of 90°C;

[0064] Add quaternary ammonium salt and active agent and continue to mix for 2 minutes, the mixer speed is 40r / min, and the mixing temperature is 90℃;

[0065] Add the mixture of reinforcing filler and coupling agent in three times, and knead for 5 minutes at a mixer speed of 50 r / min and a kneading temperature of 90°C;

[0066] Add antioxidant and plasticizer and mix for 5 minutes, the mixer speed is 50r / min, and the mixing temperature is 90℃;

[0067] Lower the mixer temperature, add the vulcanizing agent and vulcanization accelerator, and mix for 2 minutes at a mixer speed of 40 r / min and a mixing temperature of 60°C;

[0068] Binding removal, the binding temperature is 60℃, and the binding time is 3min;

[0069] Plasticate on the open mixing mill for 2 minutes, set the mixing mill roller distance to 1mm, add the rubber material and pass it thinly, make triangle packages 3 times, lower the sheet to 10mm, and leave it for 8h to obtain a section of mixed rubber.

[0070] (4) The first-stage mixed rubber obtained after the internal mixing is subjected to a second-stage open mixing, the roller spacing of the open mixing mill is 1 mm, a first-stage mixed rubber is put into the thin pass, the triangular package is made 3 times, and the sheet is reduced by 10 mm to obtain the composite insulating mixed rubber material.

[0071] (5) The obtained composite insulating rubber material is placed in a flat vulcanizer for compression vulcanization at 180° C. and 20 MPa for 15 min. After cooling to room temperature, it is placed in a blast oven and treated at 90° C. for 12 h to finally obtain the composite insulating material.

[0072] Example 2

[0073] This embodiment 2 provides a composite insulating material, the chemical composition and weight percentage of which are as follows:

[0074] EPDM rubber Dow3722P: 100 parts, white carbon black: 15 parts, kaolin: 40 parts; hexadecyltrimethylammonium bromide: 2 parts; stearic acid: 2 parts, antioxidant RD: 1 part, paraffin oil: 12 parts, silane coupling agent Si69: 2 parts, vulcanizing agent sulfur: 4 parts, vulcanization accelerator CZ: 1 part, vulcanization accelerator NS: 1 part.

[0075] The specific preparation method is the same as that in Example 1.

[0076] Comparative Example 1

[0077] This comparative example 1 provides a composite insulating material, the chemical composition and weight fractions of which are different from those of Example 1 in that quaternary ammonium salt is not added, but 5 weight fractions of zinc oxide are added instead.

[0078] The specific preparation method is the same as that in Example 1.

[0079] Comparative Example 2

[0080] This comparative example 2 provides a composite insulating material, the chemical composition and weight fractions of which differ from those of Example 2 in that no quaternary ammonium salt is added.

[0081] The specific preparation method is the same as that in Example 2.

[0082] Comparative Example 3

[0083] Comparative Example 3 provides a composite insulating material, the chemical composition and weight fractions of which differ from those of Example 2 in that 0.05 weight fractions of quaternary ammonium salt is added instead.

[0084] The specific preparation method is the same as that in Example 2.

[0085] Comparative Example 4

[0086] Comparative Example 4 provides a composite insulating material, the chemical composition and weight fractions of which differ from those of Example 2 in that 5 weight fractions of quaternary ammonium salt are added instead.

[0087] The specific preparation method is the same as that in Example 2.

[0088] Test Example 1

[0089] The mechanical properties, processing properties and electrical properties of the composite insulating materials prepared in Examples 1-2 and Comparative Examples were measured. The specific test methods are as follows:

[0090] Mooney viscosity test method: Tested in accordance with GB / T 1232.1-2016 standard;

[0091] Hardness test method: Tested in accordance with GB / T 531.1 2008 standard;

[0092] Test method for tensile strength: Tested in accordance with GB / T 528 2008 standard (dumbbell-shaped specimen);

[0093] Test method for tear strength: Test according to GB / T 529 2008 standard (right angle specimen);

[0094] AC breakdown strength: tested in accordance with GB / T 1408.1-2016 standard.

[0095] DC breakdown strength: tested in accordance with GB / T 1408.2 2016 standard.

[0096] The test results are shown in Table 1:

[0097] Table 1 Composite insulation material performance test results

[0098]

[0099] It can be seen from the above table that compared with Example 1, Example 1 adopts the quaternary ammonium salt / ethylene propylene diene monomer rubber material component combination, and the performance is significantly improved compared with the electrical performance of the zinc oxide / ethylene propylene diene monomer rubber material in Comparative Example 1. The quaternary ammonium salt helps to disperse the filler more evenly, so the AC and DC breakdown strength of the material is higher.

[0100] Compared with Example 2, Example 2 has higher mechanical properties and meets the performance index requirements. Comparative Example 2 does not contain zinc oxide and quaternary ammonium salt, and its performance is significantly lower than that of Example 2 and does not meet the technical index requirements. This is because the decomposition of the accelerator is insufficient, the scorch time and the vulcanization time are significantly prolonged, and the performance is significantly reduced.

[0101] Compared with Example 2, in Example 2, the quaternary ammonium salt is 2 parts, the mechanical properties are higher, and the performance index requirements are met. In Comparative Example 3, the quaternary ammonium salt is 0.05 parts, and its content is too small to replace zinc oxide. The final product performance is low and does not meet the technical index requirements.

[0102] Compared with Example 2, in Example 2, the quaternary ammonium salt is 2 parts, the mechanical properties are higher, and the performance index requirements are met. In Comparative Example 3, the quaternary ammonium salt is 5 parts, and the content is too high, resulting in a decrease in the crosslinking density of the rubber, making its electrical properties lower and not meeting the technical index requirements.

[0103] Test Example 2

[0104] When the composite insulating materials prepared in Example 1-2 and Comparative Example 1-2 were vulcanized, the vulcanization curves were measured by a rotorless vulcanizer, as shown in FIG. Figure 1 and Figure 2 As shown. Figure 1It can be seen that the highest torque value of Comparative Example 1 is smaller than that of Example 1, so the rubber composite material system in Example 1 forms a stronger cross-linking network with a large cross-linking density. Figure 2 It can be seen that the maximum torque value of Comparative Example 2 is smaller than that of Example 2, so the rubber composite material system in Example 2 forms a stronger cross-linked network with a large cross-linking density; on the other hand, the scorch time and vulcanization time of Comparative Example 2 are significantly prolonged, which is due to insufficient decomposition of the accelerator.

[0105] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.

Claims

1. A composite insulating material for high voltage cable accessories, characterized in that: The raw materials are composed of EPDM rubber, reinforcing filler, quaternary ammonium salt, vulcanizing agent and additives. The mass fractions of the EPDM rubber, reinforcing filler and quaternary ammonium salt meet the following requirements: Wherein, a represents the mass fraction of EPDM rubber, b represents the mass fraction of reinforcing filler, and c represents the mass fraction of quaternary ammonium salt; The raw materials of the composite insulating material do not include zinc oxide; EPDM rubber is 100 parts; The reinforcing filler is 20-80 parts; Quaternary ammonium salt is 0.12-3.6 parts; 3-5 parts of vulcanizing agent; 5.7-46 parts of additives; The reinforcing filler is at least one of white carbon black, kaolin, calcium carbonate, talcum powder or calcined clay.

2. The composite insulating material according to claim 1, characterized in that: The auxiliary agent includes:

3. The composite insulating material according to claim 2, characterized in that: The EPDM rubber has a Mooney viscosity of 20-55 MU at ML (1+4) 100°C and an ethylene content of 45-75 wt%; The quaternary ammonium salt is at least one of cetyltrimethylammonium bromide, cetyltrimethylammonium chloride, octadecyltrimethylammonium bromide or octadecyltrimethylammonium chloride.

4. The composite insulating material according to claim 3, characterized in that: The vulcanizing agent is at least one of sulfur, dicumyl peroxide or dibenzoyl peroxide; The antioxidant is at least one of antioxidant MB and antioxidant RD; The active agent is at least one of stearic acid, zinc stearate or calcium stearate; The vulcanization accelerator is at least one of diphenylguanidine, tetramethylthiuram disulfide, 2-mercaptobenzothiazole, triallyl isocyanurate, N-cyclohexyl-2-benzothiazole sulfenamide, and N-tert-butyl-2-benzothiazole sulfenamide; The plasticizer is at least one of paraffin oil, naphthenic oil or white oil; The coupling agent is a silane coupling agent.

5. The composite insulating material according to claim 4, characterized in that: The vulcanizing agent is sulfur; The antioxidant is antioxidant RD; The active agent is stearic acid; The vulcanization accelerator is at least one of diphenylguanidine, tetramethylthiuram disulfide, N-cyclohexyl-2-benzothiazole sulfenamide, and N-tert-butyl-2-benzothiazole sulfenamide; The coupling agent is at least one of bis-(γ-triethoxysilylpropyl)tetrasulfide and vinyl tris(β-methoxyethoxy)silane.

6. The method for preparing the composite insulating material according to any one of claims 1 to 5, characterized in that: The steps include: S1: Weigh the raw material components according to the ratio; S2: adding the raw materials in sequence for mixing and kneading; S3: performing a second-stage open refining on the first-stage mixed rubber obtained after the internal refining to obtain the composite insulating mixed rubber material; S4: vulcanizing and drying the obtained composite insulating mixed rubber material to finally obtain the composite insulating material.

7. The preparation method according to claim 6, characterized in that: In step S2, the mixing and kneading is specifically to put the EPDM rubber into a kneading machine, knead for 2-3 minutes, the kneading speed of the kneading machine is 30-50r / min, and the kneading temperature is 80-100°C; Add quaternary ammonium salt and active agent and continue to mix for 2-3 minutes. The speed of the mixer is 40-50r / min and the mixing temperature is 80-100℃. Add reinforcing filler and coupling agent and mix for 3-6 minutes, the mixer speed is 40-60r / min, and the mixing temperature is 80-100℃; Add antioxidant and plasticizer and mix for 2-6 minutes, the mixer speed is 40-60r / min, and the mixing temperature is 80-100℃; Lower the temperature of the internal mixer, add the vulcanizing agent and vulcanization accelerator, and mix for 2-6 minutes at a speed of 30-50r / min and a mixing temperature of 50-70℃; Debinding, debinding temperature is 50-70℃, debinding time is 1-5min; Plasticate on the mixing mill for 2-5 minutes, with the roller distance of the mixing mill being 0.5-1.5mm, add the rubber material and pass it thinly, make triangle packages 3-5 times, slice 2-15mm, and leave it for more than 6 hours to obtain a section of mixed rubber.

8. The preparation method according to claim 6 or 7, characterized in that: In step S3, specifically, the roller spacing of the mixing mill is 0.5-1.5 mm, a thin section of mixed rubber is put into the mixing mill, and the triangular package is made 3-6 times, and the sheet is 1-10 mm, so as to obtain the composite insulating mixed rubber material; In step S4, the vulcanization is performed by compression vulcanization at 120-180° C. and 10-20 MPa pressure for 10-20 min, and then cooled to room temperature; the drying is performed in a forced air oven at 70-90° C. for 12-18 h.

Citation Information

Patent Citations

  • Ethylene-propylene-diene monomer composite rubber material and preparation method thereof

    CN112321952A

  • Tire tread rubber without zinc oxide

    CN103304860A

  • Insulating rubber for ultrahigh-voltage direct-current cable accessory and preparation method thereof

    CN112250954A